Methodology for quantitative evaluation of university teaching. Application to the subject of Project Management - Cano-Moreno, Juan David; Arenas, José M.; Sánchez, Victoria; Islán, Manuel; Narbón, Julián (Procedia manufacturing, 2019)
A quantitative methodology for the assessment of a university subject has been developed, taking into account the opinion of the three agents involved in reality: students, professors and companies. The methodology is based on the concatenation of 4 matrices similar to the known House of the Quality of the Quality functions deployment (QFD) method. This methodology allows to know the degree of integration of the skills taught in the workplace. Continuous monitoring of each subject will allow to obtain a feedback about the implemented improvements based on previous results. This methodology has been applied to the Project Management university subject, which is taught in all undergraduate degrees of the School of Engineering and Industrial Design of the Polytechnic University of Madrid (UPM). Companies related to the content of the subject have collaborated through surveys. Project Management students and teachers are also participants in this study. First guidelines for improving and optimizing the relationship between university and companies have been obtained for Project Management subject.